ASSOCIATION OF ACID-BASE PARAMETERS WITH LACTATE LEVEL IN CRITICALLY ILL PATIENTS WITH METABOLIC ACIDOSIS - Donaliazarti Donaliazarti; Rismawati Yaswir; Hanifah Maani; Efrida Efrida (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Metabolic acidosis is prevalent among critically ill patients and the common cause of metabolic acidosis in ICU is lactic acidosis. However, not all ICUs can provide lactate measurement. The traditional method that uses Henderson-Hasselbach equation (completed with BE and AG) and alternative method consisting of Stewart and its modification (BDEgap and SIG), are acid-base balance parameters commonly used by clinicians to determine metabolic acidosis in critically ill patients. The objective of this study was to discover the association between acid-base parameters (BE, AGobserved, AGcalculated, SIG, BDEgap) with lactate level in critically ill patients with metabolic acidosis. This was an analytical study with a cross-sectional design. Eighty-four critically ill patients hospitalized in the ICU department Dr. M. Djamil Padang Hospital were recruited in this study from January to September 2016. Blood gas analysis and lactate measurement were performed by potentiometric and amperometric method while electrolytes and albumin measurement were done by ISE and colorimetric method (BCG). Linear regression analysis was used to evaluate the association between acid-base parameters with lactate level based on p-value less than 0.05. Fourty five (54%) were females and thirty-nine (46%) were males with participant’s ages ranged from 18 to 81 years old. Postoperative was the most reason for ICU admission (88%). Linear regression analysis showed that p-value for BE, AGobserved, AGcalculated, SIG and BDEgap were 119; 0.967; 0.001; 0.001; 0.689, respectively. Acid-base balance parameters which were mostly associated with lactate level in critically ill patients with metabolic acidosis were AGcalculated and SIG.